БАГАТОРІВНЕВИЙ ІНВЕРТОР НАПРУГИ З АМПЛІТУДНОЮ ШИРОТНО-ІМПУЛЬСНОЮ МОДУЛЯЦІЄЮ - Терещенко , Т.О.; Беженар, В.О.; Білошицький , М.Ю. (Інститут електродинаміки НАН України, Київ, 2014)
Harmonic composition of quasi-sinusoidal voltage was investigated on the six-level diode clamped inverter with amplitude pulse width modulation (APWM). Given comparison harmonic factor of stepped modulation (SM), and APWM, investigated cases of using a filter and without, given recommendations on the choice of filter cutoff frequency and APWM frequency to achieve the desired harmonic factor output voltage. Research was conducted with interactive tool Matlab-Simulink. This scientific work has described the model, presented simulation parameters and graphs based on data obtained results. References 3, figures 4.